High-Sensitivity troponin T and N-terminal pro-brain natriuretic peptide in prediction of outcome in congenital diaphragmatic hernia: results from a multicenter, randomized controlled trial - Snoek, Kitty G.; Schaible, Thomas (The journal of pediatrics, 2016)
Biomarkers may be helpful in prediction of outcomes of infants with congenital diaphragmatic hernia. The predictive value of high-sensitivity troponin T and N-terminal pro-brain natriuretic peptide was investigated in 128 infants with congenital diaphragmatic hernia. After correction for multiple testing, those biomarkers did not predict severe pulmonary hypertension, death, need of extracorporeal membrane oxygenation, or bronchopulmonary dysplasia.
Gesehen am 27.06.2019
Seitenangaben nach Vorlage: 245-249.e4